Ambient air particulate matter 10 pollutant and newly diagnosed pulmonary tuberculosis: is there any exact association? - Beuy Joob; Viroj Wiwanitkit (Egyptian Journal of Chest Disease and Tuberculosis, 2020)
Background Pulmonary tuberculosis is an important lung infection that is observable worldwide. The effect of the air pollutant on the incidence of pulmonary tuberculosis is an interesting topic. The recent research has shown that there is a possible association between ambient air pollutants, including particulate matter (PM)10, to the incidence of newly diagnosed pulmonary tuberculosis. In January 2019, the ambient air PM10 pollutant occurred in Bangkok, the capital of Thailand, a tropical endemic country of pulmonary tuberculosis. Methods The authors hereby analyzed the relationship between ambient air PM10 pollutant and newly diagnosed pulmonary tuberculosis based on the available data on January 2019. Results According to the present study, there is no association between ambient air PM10 pollutant and newly diagnosed pulmonary tuberculosis. Conclusion: In conclusion, the ambient air PM10 pollutant should not have association with incidence of pulmonary tuberculosis..